The effect of biliary obstruction, biliary drainage and bile reinfusion on bile acid metabolism and gut microbiota in mice. (3rd September 2021) - Wu, Rui; Zhang, Yangqianwen; Cheng, Qingbao; Wu, Jianmin; Zhu, Yanjing; Shi, Xuebing; Qiu, Xinyao; Yang, Shuai; Wang, Shan; Zheng, Bo; Wu, Tong; Li, Zhixuan; et al.
Abstract: Background & Aims: Preoperative obstructive jaundice is usually associated with higher post‐operative mortality. Although external biliary drainage (EBD) has been widely used to relieve obstructive jaundice, the role of bile reinfusion after EBD is still controversial. The aim of our study was to study the effects of biliary obstruction, biliary drainage and bile reinfusion on bile acid metabolism and gut microbiota. Methods: Firstly, we created a mice bile drainage collection (BDC) model to simulate the process of biliary obstruction, drainage and bile reinfusion. Then, we analysed the faecal, serum, liver and bile samples to investigate the effects of the process on bile acid profiles and gut microbiota. Finally, we evaluated the clinical effects of bile reinfusion. Results: We evaluated the bile acid profiles of faeces, serum, liver and bile of normal mice. During biliary obstruction, secondary bile acids can still be produced, and increased in the liver and serum of mice. Compared with no bile reinfusion, bile reinfusion was beneficial to the recovery of T‐ωMCA in the liver and bile, and can restore the colon crypt length shortened by biliary obstruction. Only Ruminococcus_1 proliferated when the biliary obstruction lasted for 12 days. In the clinic, bile reinfusion cannot accelerate the patient's perioperative recovery or prolong long‐term survival. Conclusion: We have successfully created a mice bile drainage collection model. Short‐term bile reinfusion can partially benefit the recovery of the secondary bile acids in the liver and bile, but hardly benefit the patient's perioperative recovery or long‐term survival. (247 words).